Analysis of Predictors Associated with Acid Suppressant Drug Related Problems (DRPs) among Inpatients at Dr. Mintohardjo Naval Hospital - Deki Yuliya Putra; Atika Wahyu Puspitasari; Siti Fauziyah (Eduvest - Journal of Universal Studies, 2026)
The use of gastric acid suppressants such as Proton Pump Inhibitors (PPI) and Histamine-2 Receptor Antagonists (H2RA) is very common in inpatient settings, but inappropriate use is often found, posing risks to patient safety and cost efficiency. This study aims to analyze the relationship of predictors (age, number of drugs, number of comorbidities, and length of stay) to the occurrence of Drug-Related Problems (DRPs) in inpatients using gastric acid suppressants. This study was an observational study with a cross-sectional design was conducted retrospectively using patient medical record data at Rumkital Dr. Mintohardjo from January to December 2024. A sample of 432 patients was taken using a simple random sampling technique based on inclusion criteria. DRPs were identified using the Pharmaceutical Care Network Europe (PCNE) V9.0 instrument. Data analysis used the chi-square test for bivariate analysis and binary logistic regression for multivariate analysis. DRP characteristics were dominated by treatment safety issues (49.1%), particularly adverse drug events, with the most frequent drug interaction being ranitidine and ketorolac. Bivariate analysis showed that length of stay (p=0.105), and number of drugs (p=0.001) significantly influenced the number of DRPs. Multivariate analysis identified the number of drugs as the most influential predictor; inpatients receiving ≥10 drugs had a 2.580 times higher risk of experiencing DRPs (p=0.003; OR 2,580; 95% CI 1.396-4.779)